An Energy-Efficient MAC Protocol in Wireless Sensor Networks: A Game Theoretic Approach. (24th June 2010) - Mehta, S.; Kwak, K. S.
Abstract : Game Theory provides a mathematical tool for the analysis of interactions between the agents with conflicting interests, hence it is well suitable tool to model some problems in communication systems, especially, to wireless sensor networks (WSNs) where the prime goal is to minimize energy consumption than high throughput and low delay. In this paper, we use the concept of incomplete cooperative game theory to model an energy efficient MAC protocol for WSNs. This allows us to introduce improved backoff algorithm for energy efficient MAC protocol in WSNs. Finally, our research results show that the improved back off algorithm can improve the overall performance as well as achieve all the goals simultaneously for MAC protocol in WSNs.